Efektifitas Pemberian Manual Terapi Dan Terapi Latihan Untuk Meningkatkan Kemampuan Fungsional Pada Penderita Osteoarthritis Knee: Case Report - Wina Rohmadhani; Totok Budi Santoso; Sugijanto Sugijanto (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Knee Osteoarthritis (OA) is a condition that occurs in the knee joint which is a progressive degenerative disease. This case can occur in all joints, usually will be experienced by someone with the age of more than 45 years, this is due to cartilage. Symptoms that often arise are stiffness in the morning and there is also crepitus when making movements in the knee. The prevalence always increases dramatically with age, which is characterized by knee pain, reduced joint range of motion, and difficulty performing daily activities. In this case, the respondent experienced pain and stiffness in the right knee. This causes respondents to have difficulty in carrying out daily activities. In this study, researchers chose physiotherapy interventions in the form of manual therapy (Knee Oscillation Traction, Mulligan Mobilization With Movement (MWM) Knee Flexion-Extension, Patellofemoral Mobilization), exercise therapy (Strengthening Flexor-Extensor Knee, Isometric Hamstring Set, Calf Rise, Functional Exercise) , cryotherapy (cold compresses) to reduce pain and also increase functional activity in patients with Osteoarthritis Knee (OA). After 8 sessions of physiotherapy intervention, there was a decrease in pain and a decrease in the disability score experienced by the patient.Keywords: Knee Osteoarthritis, Therapy Manual, Exercise Therapy, Functional Ability, Pain Reduction